What is The Role of e-system HRM, Work Environment and Job Satisfaction on SMEs Employee Performance? - Sosiady, Mulia (Journal of Industrial Engineering & Management Research, 2022)
The aim of this study is to analyze correlation of  the work environment on job satisfaction, the HR e-system on job satisfaction, work environment on employee performance, the HR e-system on employee performance and the job satisfaction on employee performance.This study uses a quantitative approach, the sampling technique uses purposive sampling, which is a sampling technique with certain considerations . The number of samples set in this study was 340  respondents of SMEs employee distributed through Google Form. Data collection techniques can be done by questionnaires and observation techniques .  Instruments use a questionnaire with a Likert scale using 5 (five) scores ranging from answers to statements provided through tools from a Scale of '1' Strongly Disagree (STS) to a Scale of '5' Strongly Agree. The data analysis technique uses a structural equation modeling (SEM). This research data processing tool uses the SmartPLS 3.0 application or software. After that, an evaluation of the SEM model is carried out to obtain and evaluate the proposed suitability and further testing will be conducted using Bootstrap resampling method developed by Geisser & Stone. The test statistic used is the t statistic (t-value) or if the p-value 0.05 (at 5 percent alpha), it is concluded that the results are significant.The conclusion of this study is The conclusion of this study is there is a direct influence between the work environment on job satisfaction, There is a direct influence between the HR e-system on job satisfaction, There is no  direct influence between the work environment on employee performance, There is no  direct influence between the HR e-system on employee performance, There is a direct effect between job satisfaction on employee performance.